2012
DOI: 10.12688/f1000research.1-61.v1
|View full text |Cite
|
Sign up to set email alerts
|

Kyasanur forest disease virus: viremia and challenge studies in monkeys with evidence of cross-protection by Langat virus infection

Abstract: Kyasanur Forest Disease Virus (KFDV), discovered in 1957, is a member of the tick-borne encephalitis virus (TBEV) complex. Diseases caused by members of the TBEV complex occur in many parts of the world. KFDV produces a hemorrhagic fever in humans in South India and fatal illnesses in both species of monkeys in the area, the black faced langur (Presbytis entellus) and the bonnet macaque (Macaca radiata). Experimental infection of the langur and the bonnet macaque with early mouse passage KFDV strain P9605 resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
2
19
1
Order By: Relevance
“…In agreement with these findings, an experimental infection studies conducted at Virus Research Centre, Pune between 1958 and 1970 found langurs to be highly susceptible to KFDV with per acute course of the disease compared to bonnet macaques. In bonnet macaques disease course was comparatively prolonged with few deaths during viremic phase and few during third week, with virus recovery from the brain similar to human biphasic disease wherein fever and signs of neurological manifestations are reported in third week 12 . Another study in bonnet macaques demonstrated, virus-specific gastrointestinal and lymphoid lesions and viral antigens in these same organs by immunohistochemistry in experimentally infected animals 11 .…”
Section: Introductionmentioning
confidence: 81%
“…In agreement with these findings, an experimental infection studies conducted at Virus Research Centre, Pune between 1958 and 1970 found langurs to be highly susceptible to KFDV with per acute course of the disease compared to bonnet macaques. In bonnet macaques disease course was comparatively prolonged with few deaths during viremic phase and few during third week, with virus recovery from the brain similar to human biphasic disease wherein fever and signs of neurological manifestations are reported in third week 12 . Another study in bonnet macaques demonstrated, virus-specific gastrointestinal and lymphoid lesions and viral antigens in these same organs by immunohistochemistry in experimentally infected animals 11 .…”
Section: Introductionmentioning
confidence: 81%
“…Bonnet monkeys ( M. radiata ) are indigenous to Southern India, where DENV circulates widely. In previous studies, Kyasanur forest disease virus (KFDV), tick-borne encephalitis virus (TBEV), Japanese encephalitis virus (JEV) and West Nile virus (WNV) have been inoculated into bonnet monkeys, resulting in high viraemia 23 – 25 . Furthermore, neutralisation antibodies have been detected after natural infection in bonnet monkeys 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The live attenuated vaccine was also tested among langurs, and although the vaccine prevented death, it could not protect against challenge infection (Bhatt & Dandawate, ; Pattnaik, ). Additionally, an attenuated Langat virus vaccine ( Langat virus is related to KFDV as they are both part of the tick‐borne encephalitis virus complex) was also tested among langurs and was found to show protection against KFDV among monkeys (Shah et al, ; Thind, ).…”
Section: Discussionmentioning
confidence: 99%